Joseph Warren Beach papers - Beach, Joseph Warren, 1880-1957.; Beach, Joseph Warren, 1880-1957.; Beach, Joseph Warren, 1880-1957.
Correspondence, diaries, lectures, writings, essays, poems, scholarly and critical notes, and other papers relating to Beach's career as a literary critic and professor of English literature at the University of Minnesota, literary subjects, and family matters. Includes material pertaining to the life and work of American and European literary figures such as Thomas Carlyle, Thomas Hardy, Henry James, George Meredith, Percy Bysshe Shelley, Thomas Wolfe, and William Wordsworth. Also includes manuscripts of books written by Beach, including The Concept of Nature in Nineteenth-Century English Poetry (1936) and The Making of the Auden Canon (1957). Family correspondents include Beach's sons, Northrop Beach and Warren Beach; and his second wife, Dagmar Doneghy. Other correspondents include Stephen T. Early, James T. Farrell, Robert Frost, George Lyman Kittredge, Harriet Monroe, Carl Sandburg, Elmer Edgar Stoll, Robert Penn Warren, and Richard Wilbur.
Literary critic and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beach, Warren -- Correspondence; Beach, Northrop, -- 1912-2002 -- Correspondence; Carlyle, Thomas, -- 1795-1881.; Doneghy, Dagmar -- Correspondence; Early, Stephen T. -- 1889-1951 -- Correspondence; Farrell, James T. -- 1904-1979 -- Correspondence; Frost, Robert, -- 1874-1963 -- Correspondence; Hardy, Thomas, -- 1840-1928.; James, Henry, -- 1843-1916.; Kittredge, George Lyman, -- 1860-1941 -- Correspondence; Meredith, George, -- 1828-1909.; Monroe, Harriet, -- 1860-1936 -- Correspondence; Sandburg, Carl, -- 1878-1967 -- Correspondence; Shelley, Percy Bysshe, -- 1792-1822.; Stoll, Elmer Edgar, -- 1874-1959 -- Correspondence; Warren, Robert Penn, -- 1905-1989 -- Correspondence; Wilbur, Richard, -- 1921- -- Correspondence; Wolfe, Thomas, -- 1900-1938.; Wordsworth, William, -- 1770-1850.; Beach family; University of Minnesota; American literature; Authors, American; Authors, European; Criticism; English literature; European literature; Literature; Critics; Educators